Alocação e dimensionamento de terminais de transbordo de soja no estado do Mato Grosso via otimização e simulação em rede de Petri P-temporizada - Gabriel Faria de Oliveira (2021)
Brazil is responsible for the food supply of more than 800 million people around the world through the export of grains. Among agricultural commodities, soybean is the main product exported, being produced on a large scale, mainly in the state of Mato Grosso, in the Center-West region of Brazil. Among a series of problems related to the grain export process, the leading role of the road modal entails high costs that have a strong impact on the economy and impede the country's greater prominence in the international market. With the adoption of alternative modes, such as waterway and rail, it is necessary to reconfigure the logistical planning for exports, with the implementation of terminals capable of delimiting the distances traveled on the highways, reducing transport costs. The purpose of this work is to present a methodology for determining the optimal location for the deployment of these terminals, from the optimization, as well as to simulate the most viable scenarios, from an economic point of view. For this, an optimization model is developed to find the ideal size and the best locations for the installation of the terminals. In addition, a P-timed Petri net simulator is created to verify the values obtained by the optimization and propose improvements. It was observed by the results, the importance of the simulation of the scenarios to verify and improve the solutions proposed by the optimization. The results point to scenarios for the better storage of soybeans from Mato Grosso destined for export, which may contribute to the improvement of Brazil's projection as a grain exporter in the international scenario.